PANDEMIC OF COVID-19 IN INDONESIA: SOCIAL POLITICS PERSPECTIVE (Pandemi Covid-19 di Indonesia: Perspektif Sosial Politik) - Shindy Diah Ayu Lestari (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
In the second half of the twentieth century, global security issues have quickly transformed into what is defined nowadays as non-traditional security issues and the latest of such non-traditional security problem has emerged recently as the recent Covid-19 pandemic impacted the whole world on an unprecedented scale. Indonesia, as the fourth most populated country with 267 million people, face an extraordinary challenge and therefore it is interesting to see and to learn how the situation developed, what the Government of Indonesia did, included what the Government should do, not only from the healthcare point of view, but also from other perspectives such as social and political. Using the problems arising during the pandemic in Indonesia as a non-traditional security issue, the present work aims to assess the difficulties faced by the country in order to establish a set of short and long term plans that should be addressed in order to improve the preparedness and to correct the current flaws generating difficulties to develop an optimal response. Governmental decisions and communication should be clear and follow a solid strategy to ensure population awareness. Law enforcement should strictly emphasize on the dangerousness of Covid-19. Coordination between central and local governments should be efficient and involve experts and respected figures. Not only healthcare but also economic, social and political issues need to be planned and projected during and after pandemic and the lessons taken during this pandemic should be used to build solid and better foundations for future development of the Republic of Indonesia.